2011
DOI: 10.1007/s12311-011-0266-1
|View full text |Cite
|
Sign up to set email alerts
|

Precerebellar Cell Groups in the Hindbrain of the Mouse Defined by Retrograde Tracing and Correlated with Cumulative Wnt1-Cre Genetic Labeling

Abstract: The precerebellar nuclei are hindbrain and spinal cord centers that send fibers to the cerebellum. The neurons of the major hindbrain precerebellar nuclei are derived from the rhombic lip. Wnt1, a developmentally important gene involved in intercellular signaling, is expressed in the developing rhombic lip. We sought to investigate the relationship between the cell clusters expressing Wnt1 and the precerebellar nuclei in the hindbrain. We therefore defined the hindbrain precerebellar nuclei by retrograde traci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 53 publications
7
40
0
Order By: Relevance
“…Wnt1 is a developmentally important gene involved in intercellular signaling that is expressed by CGNs in newborn mice [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Wnt1 is a developmentally important gene involved in intercellular signaling that is expressed by CGNs in newborn mice [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Watson and Paxinos [2010] noted the presence of a similarly positioned nucleus in a calbindin-stained section in their chemoarchitectonic atlas of the mouse brain, and the presence of the nucleus was noted in a study of mouse precerebellar nuclei [Fu et al, 2011]. However, we have found no published account of the characteristics of this nucleus in mice.…”
Section: Introductionmentioning
confidence: 75%
“…The exclusively contralateral projection character of the arcuate nucleus is the same as that of the inferior olive. In this respect, the inferior olive and the arcuate nucleus differ from the precerebellar nuclei that give rise to mossy fibers because these nuclei project either bilaterally or ipsilaterally to the cerebellum [Fu et al, 2011]. Moreover, the arcuate nucleus was found to express several biomarkers that were also expressed in the inferior olive, and which were not expressed in the mossy precerebellar nuclei (lateral reticular nucleus, pontine nuclei, external cuneate nucleus and reticulotegmental nucleus of the pons).…”
Section: The Mouse Arcuate Nucleus Is a Precerebellar Nucleusmentioning
confidence: 98%
“…Genetic strategies in mice extended the classical chick studies and revealed that dA1/Atoh1 ϩ neurons along the cRL assemble the ventral/dorsal CN and PCN (Wang et al, 2005;Okada et al, 2007;Fu et al, 2009Fu et al, , 2011Rose et al, 2009b). Application of intersectional/subtractive fate-map approaches further identified the contribution of rhombomere-specific interneurons to these nuclei (Farago et al, 2006;Maricich et al, 2009).…”
Section: Axonal Patterns Targets and Connectivity Of Da1-interneuronsmentioning
confidence: 90%